2014
DOI: 10.1016/j.nano.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of vascular endothelial growth factor improves stem cell therapy in a rat myocardial infarction model

Abstract: Rebuilding of infarcted myocardium by mesenchymal stem cells (MSCs) has not been successful because of poor cell survival due in part to insufficient blood supply after myocardial infarction (MI). We hypothesize that targeted delivery of vascular endothelial growth factor (VEGF) to MI can help regenerate vasculature in support of MSC therapy in a rat model of MI. VEGF-encapsulated immunoliposomes targeting overexpressed P-selectin in MI tissue were infused by tail vein immediately after MI. One week later, MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
(46 reference statements)
1
26
0
1
Order By: Relevance
“…In the cell therapy space, liposomes were shown to be efficient for the targeted delivery of growth factors such as vascular endothelial growth factor (VEGF (Tang et al, 2014)), VEGF aptamers (Willis et al, 1998) and endothelial growth factor (EGF (Alemdaroglu et al, 2008)) as well as small interfering RNA (siRNA (Wang et al, 2013)). Tang et al (2014) recently developed VEGF-encapsulated immunoliposomes targeting myocardial infarction (MI).…”
Section: Liposomes In Clinical Usementioning
confidence: 99%
See 1 more Smart Citation
“…In the cell therapy space, liposomes were shown to be efficient for the targeted delivery of growth factors such as vascular endothelial growth factor (VEGF (Tang et al, 2014)), VEGF aptamers (Willis et al, 1998) and endothelial growth factor (EGF (Alemdaroglu et al, 2008)) as well as small interfering RNA (siRNA (Wang et al, 2013)). Tang et al (2014) recently developed VEGF-encapsulated immunoliposomes targeting myocardial infarction (MI).…”
Section: Liposomes In Clinical Usementioning
confidence: 99%
“…Tang et al (2014) recently developed VEGF-encapsulated immunoliposomes targeting myocardial infarction (MI). By injecting the VEGF-immunoliposomes together with mesenchymal stem cells (MSCs) into a rat immediately following MI, the authors observed a remarkably high attenuation in cardiac function loss, together with an 80% increase in blood vessel density.…”
Section: Liposomes In Clinical Usementioning
confidence: 99%
“…Priming MSCs with these trophic factors has been reported to enhance cell survival and retention. Recently, Tang et al [133] reported that exogenously expressed VEGF promoted myocardial repair at least in part through SDF-1a/CXCR4-mediated migration of CSCs. Similarly, CSCs treated with SDF-1a demonstrated better engraftment and retention at the infarcted area as well as higher levels of proliferation.…”
Section: Preconditioning Of Stem Cells To Enhance Stem Cell Efficacymentioning
confidence: 99%
“…31 Briefly, all four lipid components were dissolved in chloroform (Sigma-Aldrich), which was then removed by nitrogen gas purging at room temperature, followed by overnight evaporation in a Labconco Freezone 1 freeze-dryer (Kansas City, MO, USA). The resulting lipid film was hydrated with a 250 mM ammonium sulfate (SigmaAldrich) solution by gentle mixing, resulting in spontaneously organized multilamellar vesicles (MLVs).…”
Section: Preparation Of Liposomal Bevacizumab and Immunoliposomal Doxmentioning
confidence: 99%